Toward a theoretical framework for studying climate change policies: insights from the case study of Singapore - Ng, Ai Sian (2018)
The world decided in December 2015 to take actions to reduce global warming. To contribute toward this goal, this research examines possible policy levers for inclusion in the climate change ratification plan. A case study of the measures taken by the Republic of Singapore, a low-lying 719.2 km2 island without natural resources in Asia, is conducted. Being vulnerable to climate change impact and yet having to balance her people’s needs and economic progress with limited resources, the measures taken by this small country could offer policy insights for small states and states without access to alternative energy sources. This research analyzes the online policy documents posted by eleven organizations to answer the main research question of identifying policy levers as theoretical constructs to form a framework that can be used to study climate change policies. A qualitative data analysis software, QSR NVivo 10, is used to classify the proposed nodes developed by the researchers using a system perspective integrating the insights from the key international climate change frameworks with the theoretical concepts from the model of pro-environmental behavior. The findings can offer insights toward developing a new contextual influence framework, which can help strengthen policy development and outcome measurement.